Students' learning style of school of medical sciences, Universiti Sains Malaysia - Barman, Arunodaya; Jaafar, Rogayah (2008)
Learning style defines how a learner perceives, interacts with, and responds to the learning environment (Keefe, 1979). Learning style varies with the personality style. As learning style is individualized, there is possibility of wide variation in the learning style even in a specific group of students. Knowing students' learning style may help the teachers create an appropriate learning situation (Amin, 2000). Thus it is important to identify the learning styles of students for designing learning instruction for better performance of the students. VARK learning style inventory was used to explore the learning styles of medical students of Universiti sains Malaysia. All 988 undergraduate medical students of year 1 to year 5 MD program were the study population. Seven hundred and thirteen students responded to the learning style inventory, giving a response rate of 72% .Out of 713 respondents 510 (71.53%) preferred single, 148 (20.76%) preferred two, 54 (7.57%) preferred three and 1 (10%) preferred four learning styles. Single majority of Malay students (24.8%) preferred read/write learning style when single majority of Chinese (26.1%) and Indian (40.0%) preferred kinesthetic learning style. Single highest percentage (24.6%) of female respondents preferred read/write learning style when single highest percentage (25 .3%) of male respondents preferred kinesthetic learning style.